LET’S TALK AND TOLERATE: STRENGTHENING STUDENTS CULTURAL AWARENESS THROUGH LITERATURE CIRCLES - Moecharam, Nicke Yunita; KartikaSari, Della Nuridah (Universitas Pendidikan Indonesia, 2014)
Abstract: Putting more attention on teaching language skills, the use of literature in EFL classrooms is often abandoned. While essentially, exploiting literary texts in some advanced EFL courses, serves a variety of purposes, dedicated to encourage interactive and communicative classes for language learners at different levels of proficiency. Literary texts often offer cultural explorations through the embedded cultural contexts in the stories. Indeed, exploring literary works provides an exercise in cultural relativity, so that students are more aware of the cultural differences presented in various contexts. Both teachers and students need to get involved in class discussions and activities which are created to support deep exploration of cultures in the texts. This paper reports on the use of literature circles in an advanced EFL classroom to reinforce students‘ cultural awareness through the examination of classic literatures as well as contemporary realist fiction. The two genres of literatures also bring about multicultural issues which are worth noting in an attempt of developing students‘ cutural awareness. In the research, it is further found that distributing students in small discussion groups has encouraged more ―talking‖ and improved students‘ written responses. In addition, teachers discovered that cultural values and attitudes are easily transferred through the characters in the literary works.Keywords: literature circles in EFL classroom, classic literatures, contemporary realist fictions.